Management of Information and Communication Technology and Teachers’ Work Performance in Secondary Schools in Cross River State, Nigeria - Etor, Comfort R.; Mbon, Usen F.; Ekanem, E. E. (Mediterranean Journal of Social Sciences, 2020)
The aim of the study was to investigate the relationship between management of Information and Communications Technology (ICT) and teachers’ work performance in secondary schools in Cross River State, Nigeria. To achieve the purpose of the study, two research questions and one null hypothesis were formulated to guide the study. Survey research design was adopted for the study. The population of the study comprised of 5288 teachers in all the 271 public secondary schools in Cross River State, Nigeria. A sample of 800 teachers was drawn using stratified and simple random sampling techniques. Two instruments titled: Management of Information and Communications Technology Questionnaire (MICTQ) and Teachers’ Work Performance Questionnaire (TWPQ) were used to collect data from the respondents. Data was analyzed using Pearson Product Moment Correlation at .05 level of significance and 798 degrees of freedom. The finding revealed that among the 12 principals’ ICT management practices, only cleaning/dusting, arrangement of facilities and ventilation of ICT centres were significant. A positive significant relationship between Information and Communication Technology and teachers’ work performance was also established (p < .05). Based on the finding, it was recommended amongst others that, there should be adequate supply of ICT facilities to secondary schools for effective utilization by teachers and students for quality teaching and learning.